Gaseous Ion Mobility, Diffusion, and Reaction - Viehland, Larry A. (Springer Series on Atomic, Optical, and Plasma Physics,, 2018)
This book is about the drift, diffusion, and reaction of ions moving through gases under the influence of an external electric field, the gas temperature, and the number density. While this field was established late in the 19th century, experimental and theoretical studies of ion and electron swarms continue to be important in such varied fields as atomic and molecular physics, aeronomy and atmospheric chemistry, gaseous electronics, plasma processing, and laser physics. This book follows in the rigorous tradition of well-known older books on the subject, while at the same time providing a much-needed overview of modern developments with a focus on theory. Graduate students and researchers new to this field will find this book an indispensable guide, particularly those involved with ion mobility spectrometry and the use of ion transport coefficients to test and improve ab initio ion-neutral interaction potentials. Established researchers and academics will find in this book a modern companion to the classic references.